Implementasi Program Keluarga Harapan (PKH) Dalam Mengatasi Kemiskinan - Karningsih Karningsih; Christine Diah Wahyuningsih (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2024)
This study uses a qualitative research method with data collection techniques using observation, interviews and documentation. Research informants are determined purposively. Factors for the implementation of PKH are good communication between implementers and PKH recipients, as well as with the support of resources that have been provided by the government, both from human resources and financial resources. The open attitude of program implementers in providing information on the use of funds so that they are not misused. Meanwhile, the inhibiting factor for the implementation of PKH is that the data on beneficiaries of the Family Hope Program (PKH) is not on target. The implication of this policy is that assistance is still needed for PKH beneficiary communities to be further improved, as well as the existence of a bureaucratic structure in each region or environment of PKH beneficiary communities so that data updates can be well integrated, and carried out periodically and sustainably.